Unique Solution of a Coupled Fractional Differential System Involving Integral Boundary Conditions from Economic Model - Rui Li; Haoqian Zhang; Hao Tao (Abstract and Applied Analysis)
We study the existence and uniqueness of the positive solution for the fractional differential system involving the Riemann-Stieltjes integral boundary conditions , , , , , and , where , , and and are the standard Riemann-Liouville derivatives, and are functions of bounded variation, and and denote the Riemann-Stieltjes integral. Our results are based on a generalized fixed point theorem for weakly contractive mappings in partially ordered sets.